Can Portugal escape stagnation without opting out from the Eurozone? - Pedro Leao; Alfonso Palacio-Vera (Levy Economics Institute of Bard College, 2011)
The creation of the Economic and Monetary Union (EMU) has not brought significant gains to the Portuguese economy in terms of real convergence with wealthier eurozone countries. We analyze the causes of the underperformance of the Portuguese economy in the last decade, discuss its growth prospects within the EMU, and make two proposals for urgent institutional reform of the EMU. We argue that, under the prevailing institutional framework, Portugal faces a long period of stagnation, high unemployment, and painful structural reform, and conclude that, in the absence of institutional reform of the EMU, getting out of the eurozone represents a serious political option for Portugal.
Keywords: E32; E65; F32; F41; J50; 330; nominal wage cuts; Eurozone; relative unit labor costs; zero-sum game